Using a videogame to facilitate nursing and medical students' first visit to the operating theatre. A randomized controlled trial. (August 2017) - del Blanco, Ángel; Torrente, Javier; Fernández-Manjón, Baltasar; Ruiz, Pedro; Giner, Manuel
Abstract: Background: First experiences in the operating theatre with real patients are always stressful and intimidating for students. We hypothesized that a game-like simulation could improve perceptions and performance of novices. Methods: A videogame was developed, combining pictures and short videos, by which students are interactively instructed on acting at the surgical block. Moreover, the game includes detailed descriptive information. After playing, students are given feedback on their performance. A randomized controlled trial was conducted with 132 nursing and medical students with no previous experience in surgery. Sixty two (47.0%) were allocated to a control group (CG) and 70 (53.0%) to an experimental group (EG). Subjects in EG played the game the day prior to their first experience in the theatre; CG had no access to the application. On the day after their experience at surgery, all students filled in a questionnaire in a 7-point Likert format collecting subjective data about their experience in the surgical block. Four constructs related to students' feelings, emotions and attitudes were measured through self-reported subjective scales, i.e. C1: fear to make mistakes, C2: perceived knowledge on how to behave, C3: perceived errors committed, and C4: attitude/behaviour towards patients and staff. The main research question was formulated as follows: do students show differences in constructs C1–C4 by exposure to the game? Results: EG reported statistically significant higher scores on the four aspects measured than CG ( p  < 0.05; Mann-Whitney U tests; Cohen's d standardized effect size d1 = 0.30; d2 = 1.05; d3 = 0.39; d4 = 0.49). Conclusions: Results show clear evidence that the exposure to the game-like simulation had a significant positive effect on all the constructs. After their first visit to the theatre, students in EG showed less fear (C1) and also perceived to have committed fewer errors (C3), while they showed higher perceived knowledge (C2) and a more collaborative attitude (C4). Highlights: First experiences in the operating theatre with real patients are always stressful. A game-like simulation could improve perceptions and performance of novices. A videogame was developed, combining pictures and short videos. A randomized controlled trial was conducted with nursing and medical students. The videogame had positive effects on fear, knowledge, errors and attitude/behavior.